Effect of Incident Angle of Wear-Ring Clearance on Pressure Pulsation and Vibration Performance of Centrifugal Pump - Jia, XiaoQi; Yu, Jilin; Li, Bo; Zhang, Li; Zhu, ZuChao (Frontiers in Energy Research, 2022)
Wear-ring is an important part of the centrifugal pump. The leakage flow in wear-ring clearance and the main flow at impeller inlet form crossed mixed flows perpendicular to each other. Large eddies and shocks are produced at the intersection of the two flows due to great velocity difference and different directions, resulting in flow losses, unsteady flow and even flow-induced vibration. Consequently, pump performance, pressure pulsation and vibration and other characteristics will be greatly affected. In this paper, 5 incident angles between the incident section of the wear-ring clearance and the circumferential direction of impeller inlet, i.e. the original angle (90°), 75°, 60°, 45° and 30°, were formed with a low specific speed centrifugal pump as the study object. Unsteady flow calculation and fluid-structure interaction (FSI) calculation were performed on centrifugal pumps with different wear-ring clearances; the effect of incident angle of wear-ring clearance on the distribution of pressure pulsation and vibration performance of centrifugal pump was analyzed. The results showed that the improved efflux angle of wear-ring clearance could effectively weaken the impact disturbance of the leakage flow in wear-ring clearance to the main flow at the inlet. Accordingly, the flow status at the inlet of the centrifugal pump was improved; flow losses were reduced; the efficiency of the centrifugal pump was improved; and the vibration amplitude and vibration energy of the pump were also reduced.